Calidad e integración exitosa de la cadena automotriz de las PYMES en el estado de Nuevo León Quality and successful integration of the automotive supply chain companies in the state of Nuevo León - Blanco Jiménez, Mónica; Guerra Moya, Sergio Armando; Villalpando Cadena, Paula; Castillo Villarreal, Jorge (Facultad de Contaduría Pública y Administración U.A.N.L., 2011)
Abstract. Small and medium enterprises in the automotive industry in Mexico play an increasingly important role in the development of national industry, contributing to 2.6% of GDP and represent 11.5% of the manufacturing sector. However, in a recent study of TBM Consulting found that only 20% of auto parts manufacturers in Mexico have the potential to become world-class suppliers of the automotive industry, 40% are in the process of improvement and the remaining 40%, still doing things the traditional way. According to this analysis, including the difficulties faced by SMEs are unable to comply with the requirements of quality products, poor marketing, lack of refinancing, lack of efficient management techniques, among others. In this research is to analyze the problems of SMEs in the automotive sector in the State of Nuevo León and whether having a system implementation of 5S's is looking to integrate the methodologies needed to be innovative, strengthen intercompany and to adopt the ABC costing accounting system, allowing them to have a better quality and successful integration in the automotive supply chain in Nuevo Leon.